Estrategias de enseñanza aprendizaje para el área de lengua y literatura en estudiantes con trastornos de lenguaje de Educación General Básica - Caza Tipantasig, María José (2025)
This study, entitled "Teaching-Learning Strategies for Students with Language Disorders in Language and Literature", focuses on addressing the specific educational needs of students with functional dyslalia. The research will be conducted with a group of 9th-grade students, aged between 12 and 13 years, in an educational institution in Guayaquil, Ecuador. The primary objective of the research is to determine how language and literature teaching can be effectively adapted for students with phonological disorders. To achieve this, a mixed approach methodology will be implemented, combining quantitative and qualitative methods, utilizing tools such as theoretical methods (inductive, deductive, and analytical) and empirical methods (observation and measurement). Data collection will be carried out using techniques such as direct observation, teacher interviews, and student and parent surveys. A teaching-learning strategy program is proposed that includes pronunciation exercises, guided reading, individual teacher support, and educational technology integration. The expected results aim to identify the impact of functional dyslalia on learning, design personalized pedagogical strategies, create an inclusive learning environment, and foster collaboration among teachers, students, and families. The research concludes that functional dyslalia significantly impacts language and literature learning. The study emphasizes the need for a personalized and comprehensive educational approach, with adapted pedagogical strategies, a comprehensive learning environment, strategic use of technology, and collaboration between teachers, students, and families.